(untitled) (Tanzania Medical Journal, 2007)
Birth weight is known to influence morbidity and mortality. Simple measures to predict birth weight before delivery would therefore be useful in order to plan a delivery. Maternal parturient symphysio-fundal height has been used to detect Low Birth Weight. This study aims at predicting the fetal weight using the maternal symphysio-fundal height and abdominal girth. A prospective study was done on 600 pregnant women admitted in labor. A detail anthropometric measurement was done and correlated with birth weight after delivery. Symphysio-fundal height and abdominal girth measured to the nearest centimeter positively correlated with birth weight. The coefficient of correlation was 0.74 and 0.69 respectively with a significance of p0.295). A formula was derived for the estimation of birth weight using these two parameters viz: Birth weight = Bo + B1 (Abdominal girth) + B2 (symphysio-fundal height) where B0 is a constant =2.61, B1 (partial regression coefficient) = 0.32 (Standard deviation 0.002) and B2 (partial regression coefficient) = 0.081 (Standard deviation 0.004). The sensitivity in detecting birth weight below 2 kg was 88.2% and the specificity was 84.3%. While the specificity for detecting birth weight above 3.8kg was 83.3% and a specificity of 68%. The Symphysio-fundal height and abdominal girth could predict the birth weight more closely than the gestational age. Keywords: Symphysio-fundal height, abdominal girth, parturient, prediction, birth weight. Tanzania Medical Journal Vol. 19 (1) 2004: pp.